Emotional Intelligence through Soft Skills for Employability - Lekshmy , S N; Hukkeri, Sheetal V; Manju Priya, R; Fathima, Y (Apex Journal of Business and Management, 2025)
Emotional intelligence (EI) plays a vital role in enhancing employability through the development and application of soft skills. EI refers to the ability to understand, manage, and harness one’s own emotions and those of others. In the workplace, high EI helps in navigating complex social environments, fostering teamwork, and maintaining positive professional relationships. Core aspects of EI, such as self-awareness, self-regulation, motivation, empathy, and social skills, significantly contribute to soft skills that are crucial for employability. Soft skills encompass communication, teamwork, problem-solving, adaptability, and conflict resolution. Individuals with strong EI are better equipped to communicate effectively, resolve conflicts amicably, and adapt to changing circumstances. They can empathetically understand colleagues and clients, leading to better collaboration and customer satisfaction. Employers highly value these skills, as they are instrumental in creating a harmonious and productive work environment. By investing in the development of EI, individuals can improve their employability, making them more attractive candidates for prospective employers. This demonstrates the integral relationship between emotional intelligence and the cultivation of soft skills essential for career success.